Wild harbour porpoises startle and flee at low received levels from acoustic harassment device - Elmegaard, Siri L.; Teilmann, Jonas; Rojano-Doñate, Laia; Brennecke, Dennis; Mikkelsen, Lonnie; Balle, Jeppe D.; Gosewinkel, Ulrich; Kyhn, Line A.; Tønnesen, Pernille; Wahlberg, Magnus; Ruser, Andreas; Siebert, Ursula; et al. (Scientific Reports, 2023)
Acoustic Harassment Devices (AHD) are widely used to deter marine mammals from aquaculture depredation, and from pile driving operations that may otherwise cause hearing damage. However, little is known about the behavioural and physiological effects of these devices. Here, we investigate the physiological and behavioural responses of harbour porpoises (Phocoena phocoena) to a commercial AHD in Danish waters. Six porpoises were tagged with suction-cup-attached DTAGs recording sound, 3D-movement, and GPS (n = 3) or electrocardiogram (n = 2). They were then exposed to AHDs for 15 min, with initial received levels (RL) ranging from 98 to 132 dB re 1 µPa (rms-fast, 125 ms) and initial exposure ranges of 0.9-7 km. All animals reacted by displaying a mixture of acoustic startle responses, fleeing, altered echolocation behaviour, and by demonstrating unusual tachycardia while diving. Moreover, during the 15-min exposures, half of the animals received cumulative sound doses close to published thresholds for temporary auditory threshold shifts. We conclude that AHD exposure at many km can evoke both startle, flight and cardiac responses which may impact blood-gas management, breath-hold capability, energy balance, stress level and risk of by-catch. We posit that current AHDs are too powerful for mitigation use to prevent hearing damage of porpoises from offshore construction.